Digital Artery Perforator-Based Propeller Flaps for Fingertip Defects: Clinical Evaluation and Reconstructive Considerations (Cuestiones de Fisioterapia, 2024)
Background: Fingertip injuries are common hand trauma presentations and may cause functional, sensory, and aesthetic impairment when reconstruction is inadequate. Digital artery perforator-based propeller flaps provide local, vascularized, sensate-compatible tissue while preserving the main digital artery and avoiding staged procedures.This review evaluates the anatomical basis, reconstructive indications, surgical principles, clinical outcomes, advantages, limitations, and complications of digital artery perforator-based propeller flaps for fingertip defect reconstruction